A lógica da fantasia e mais além - Virgínia Célia Carvalho da Silva (2020)
The present investigation is constituted from the hypothesis that the Lacanian formalization of the concept of sinthome introduces a new conceptualization of the end of analysis which is neither dichotomous nor does it set aside the fantasy theory. There are discontinuities but no opposition between fantasy’s crossing and the identification of sinthome. In this sense, we consider that there would be “something beyond fantasy”, which evidences that the sinthome does not exclude fantasy, even though it goes beyond. Starting from a study on the notion of fantasy in Sigmund Freud, Jacques Lacana and Lacques-Allain Miller, maintaining as a reference the transmission obtained by reading of the reports on the pass dispositive which bear witness to the psychoanalytical experience, we were able to conclude that fanta-sy is also present in the sinthome, in a movement that also includes the pulsion. Our journey allowed us to confirm the thesis that even after the elaborations on the sinthome, locating the logic in fantasy in neurosis is still maintained as a fundamental clinical operator. Not only constituting itself as a key in the subjects’ repetitions, fantasy is what gives matter to poetry (Lacan, 1977). In this sense, the pass testimonials directed us to a poetic at the end of analysis, seeing as they demonstrate how a manner of singular satisfaction can touch the social bond. Fantasy, at the same time as it is presented in its imaginary vertent, full of meaning, also possess a symbolic dimension very strongly linked to the signifier. However, it is its real vertent, “pas-de-sens”, that highlights the ballet between fantasy and drive pre-sent in the sinthome.